Direct or Collateral Liver Damage in SARS-CoV-2–Infected Patients - Lizardo-Thiebaud, Maria J.; Cervantes-Alvarez, Eduardo; Limon-de la Rosa, Nathaly; Tejeda-Dominguez, Farid; Palacios-Jimenez, Mildred; Méndez-Guerrero, Osvely; Delaye-Martinez, Marco; Rodriguez-Alvarez, Fatima; Romero-Morales, Beatriz; Liu, Wei-Hui; Huang, Christene A.; Kershenobich, David; Navarro-Alvarez, Nalu (Seminars in Liver Disease, 2020)
Liver injury can result from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection with more than one-third of COVID-19 patients exhibiting elevated liver enzymes. Microvesicular steatosis, inflammation, vascular congestion, and thrombosis in the liver have been described in autopsy samples from COVID-19 patients. Several factors, including direct cytopathic effect of the virus, immune-mediated collateral damage, or an exacerbation of preexisting liver disease may contribute to liver pathology in COVID-19. Due to its immunological functions, the liver is an organ likely to participate in the viral response against SARS-CoV-2 and this may predispose it to injury. A better understanding of the mechanism contributing to liver injury is needed to develop and implement early measures to prevent serious liver damage in patients suffering from COVID-19. This review summarizes current reports of SARS-CoV-2 with an emphasis on how direct infection and subsequent severe inflammatory response may contribute to liver injury in patients with and without preexisting liver disease.
Keywords: liver; SARS-CoV-2; COVID-19; ACE2; inflammasome